Implementación de la herramienta virtual - Chamilo- en la metodología de aprendizaje del español en primer grado de la I.E. Domingo Irurita, sede Santa Teresita en Palmira, Valle (2019)
With the aim to improve both the students’ communication skills and the results of the different national (SABER test) and international (PISA test) standardized tests, four thematic units were implemented by means of the “Chamilo” virtual tool to teach Spanish to students of the first grade of the Institución Educativa Domingo Irurita, Santa Teresita in Palmira, Valle del Cauca. A qualitative type methodology, specifically the case study modality, was used in this investigation. The pedagogical model considered was the Ausubel’s significant learning model. It was found that most of the students did not have access to the TIC (information and communication technologies) from home. It was noticed that the implementation of the didactic sequence in the classroom contributed to the significative learning process of Spanish, allowing the students to acquire the respective knowledge in a more pleasant way and within less time than with the use of traditional methods. Keywords: Chamilo platform, communication skills, learning, ICT tools, virtual tools.